2017
DOI: 10.1063/1.4983418
|View full text |Cite
|
Sign up to set email alerts
|

An observation of histological evidence on internal organ damages in mice caused by repeated exposures to motorcycle emissions

Abstract: Abstract. Motor vehicle emissions have been identified as a source of ultrafine particles, which have significant impacts on human health. Repeated and prolonged exposure to ultrafine particles may have a significant association with organ damage. Here, we evaluated the correlation between repeated exposure to ultrafine particles and organ damage in mice. Motorcycle emissions were injected into an exposure chamber with mice for a period of 20 seconds. This treatment was conducted over 10 days. The mice were sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…In each field, the number of normal and abnormal tubular epithelial cells were counted, while the level of Bowman’s space was measured ( Fig. 2 ) [ 18 ]. Normal tubular epithelial cells had no edema and vacuolation [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…In each field, the number of normal and abnormal tubular epithelial cells were counted, while the level of Bowman’s space was measured ( Fig. 2 ) [ 18 ]. Normal tubular epithelial cells had no edema and vacuolation [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The changes in the mice liver include the central vein, hepatocyte cell form, and sinusoid blood vessel (Fig. 7) [9]. The centralist vein shape that is originally a spherical shape and unbroken.…”
Section: Liver Damagementioning
confidence: 99%
“…Pollutants can pass through the body through respiration and oral processes. The presence of pollutants in the body will be able to disrupt the function of organs, including the kidney as the main organ in the excretory system [6,7], the lungs as respiratory organs [8], the liver that plays an important role in the process of detoxification, and blood as the most fluid in the body [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This study has established that it is very important to determine particles size (pad particles) to investigate the risk of deposition into the respiratory tract during inhalation, causing particles connected with posing hazards to oxidative stress and inflammation (10). Other researchers have shown that ultrafine particles may become bloodborne and translocate to other tissues such as the liver, kidneys, and brain (11).…”
Section: Introductionmentioning
confidence: 99%